The Tabernacle and Creation Theology in the Midst of Covid-19 Pandemic in Asia - Nikolas Kristiyanto (Journal of Asian Orientation in Theology, 2021)
The important question in this article is “How important is the construction of the tabernacle, on the sanctuary texts, especially in Exod 39:32-43 (in the larger context of Exod 25-31.35-40), for our church today, especially in Asia – in the midst of Covid-19 pandemic?”  Therefore, this article tries (1) to develop some theological thoughts of the Construction of Tabernacle in Exod 39:32-43 for Our Church Today; (2) to explore their theological implications for our situation today – in the midst of Covid-19 pandemic; and (3) to improve some theological thoughts on “Tabernacle” in the Catholic Church, especially regarding Sacramentum Caritatis 69 which describes the location of the tabernacle in the church by using the strong words, “The correct positioning of the tabernacle”. We try to go deeper on it by examining the richness of theological thoughts behind “the tabernacle” – not just focus on “the location” but try to go beyond.